2006
DOI: 10.1002/ptr.1939
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity on HIV‐1 reverse transcriptase and integrase of a carmalol derivative from a brown Alga, Ishige okamurae

Abstract: The bioassay-directed isolation of a marine brown alga, Ishige okamurae, afforded a carmalol derivative, diphlorethohydroxycarmalol. This compound exhibited inhibitory effects on HIV-1 reverse transcriptase and integrase with IC(50) values of 9.1 microM and 25.2 microM, respectively. However, diphlorethohydroxycarmalol did not show an inhibitory activity against HIV-1 protease. Moreover, diphlorethohydroxycarmalol nonaacetate obtained by acetylation and fucosterol failed to show any inhibitory activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 11 publications
0
28
0
1
Order By: Relevance
“…The primary mode of action for lamivudine and zidovudine is the termination of the DNA chain after incorporation into the viral genome. While as for sulfated polysaccharides, several researches reveal that its antivirus mechanism was mainly due to: (1) block viral entry into host cells by interfering with the attachment of virus to the cell-surface receptors [15,16]; (2) inhibit reverse transcriptase [17]; and (3) improve the immune function [18].…”
Section: Tablementioning
confidence: 99%
“…The primary mode of action for lamivudine and zidovudine is the termination of the DNA chain after incorporation into the viral genome. While as for sulfated polysaccharides, several researches reveal that its antivirus mechanism was mainly due to: (1) block viral entry into host cells by interfering with the attachment of virus to the cell-surface receptors [15,16]; (2) inhibit reverse transcriptase [17]; and (3) improve the immune function [18].…”
Section: Tablementioning
confidence: 99%
“…[25] showed that Ishige okamurae Yendo-derived diphlorethohydroxycarmalol also has an inhibitory effect on HIV-1. This compound exhibited inhibitory effects on the HIV-1 reverse transcriptase and integrase with IC 50 values of 9.1 μM and 25.2 μM, respectively.…”
Section: Potential Marine-derived Anti-hiv Agents and Their Anti-hmentioning
confidence: 99%
“…It is found throughout the upper and middle intertidal zones on rough open coast in Korea (Cho et al, 2008). I. okamurae and its phlorotannins have been reported to have many useful bioactivities including anticoagulative, antioxidant, and HIV-1 reverse transcriptase and bacterial phospholipase A 2 inhibitory activities (Heo et al, 2008;Zou et al, 2008;Ahn et al, 2006;Cho et al, 2008).…”
Section: Introductionmentioning
confidence: 97%